Gūnahā-i naṯr-i fārsī dar ʿaṣr-i Qāǧār - Ḥāǧǧ Bābāyī, Muḥammad Riḍā (Intišārāt-i Ḥikāyat-i Qalam-i Nuvīn, 2015)
Persian prose literature - 19th century ; Persian prose literature - 19th century - History and criticism
Keywords: Persisch; Literatur; Geschichte